Le site emporté par l’image ? - Lucinda Groueff; Sonia Keravel (Projets de Paysage)
The evolution of digital practices is constantly increasing the number of images available to us, both in terms of their visibility and their production. This is radically changing the way we understand and teach landscape architecture. The question is no longer how to produce an image, but what the image produces. Teaching landscape architecture requires transmitting the codes and references pertaining to the different fields of visual culture which underpin a changing culture of landscape architecture in tune with social mutations. How do these new relationships with images, facilitated by digital practices transform architectural approaches? What changes do they imply in teaching landscape architecture? These notions will be developed in the light of the experience of the last three years of teaching (2021-2024) at the École nationale supérieure de paysage de Versailles, specifically through the productions of and the process designed for the Fond d’écran workshop. We will demonstrate how, by working the image, students initiate a landscape project and discuss contemporary representations of a new city using digital practices.